Retinoic acid prevents ventricular remodelling induced by tobacco smoke exposure in rats - Oliveira, Lucienne C. [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Rafacho, Bruna P. M. [UNESP]; Duarte, Daniella R. [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP] (Acta Cardiologica, 2011)
Objective Our objective was to test the hypothesis that retinoic acid supplementation could attenuate ventricular remodelling induced by tobacco smoke exposure in rats.Methods and results Wistar rats were allocated into three groups: control (C, n = 8); exposed to tobacco smoke (ETS, n = 9); exposed to tobacco smoke and all-trans-retinoic acid (ETS-RA, n = 9). After two months, cardiac function and geometry were assessed by echocardiography, and geometry changes were confirmed by morphometric analysis. Data are expressed as mean +/- SD or medians (including the lower quartile and upper quartile). ETS showed higher normalized left ventricular diastolic diameters than groups C and ETS-RA (C = 18.4 +/- 3.57 mm/kg, ETS = 23.0 +/- 1.8, ETS-RA = 19.5 +/- 0.99; P < 0.05) and systolic diameters (C = 8.25 +/- 2.16 mm/kg, ETS = 11.5 +/- 1.31, ETS-RA = 8.25 +/- 0.71 mm/kg; P < 0.05). ETS showed reduced ejection fraction (C = 91 +/- 2.0, ETS = 87 +/- 3.0, ETS-RA = 92 +/- 3.0; P < 0.05) and fractional shortening (C = 55.8 +/- 4.41 %, ETS = 49.7 +/- 4.43 %, ETS-RA = 57.6 +/- 5.15 %; P = 0.01) compared to C and ETS-RA. ETS had increased myocyte cross-sectional area (C = 294 +/- 21 mm2, ETS = 352 +/- 44, ETS-RA = 310 +/- 35; P < 0.05) compared to C and ETS-RA. Considering all variables, there were no differences between groups C and ETS-RA.Conclusion Retinoic acid prevented ventricular remodelling induced by tobacco smoke exposure.
Keywords: Remodelling; heart failure; myocardial hypertrophy; smoking